Rain rate distribution for satellite to earth microwave links design in Libya - Budalal, Asma. Ali H.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ahmed, Musse Mohamud (IEEE, 2016)
Satellite to earth links operating at Ku, Ka, and V bands are strongly attenuated by rain. Rain attenuation is the most significant parameter which degrades the performance of the links. Hence, it is essential for satellite link designer to take into account rain fade prediction accurately before system implementation. Rain rate is the main parameter to predict of rain attenuation. Rainfall statistical data measured and recorded in Libya with 3-hours integration time for the period of 30 years are collected. The prediction methods require one minute integration time rain intensity. Hence, collected data were analyzed and processed to convert into one –minute rain rate cumulative distribution in Libya. Several prediction models have been utilized for conversion with consideration of the climatic condition of the study case area. One prediction model was recommended to predict one-minute rain rate distribution for microwave link design in Libyan environment. The converted rain rate data are used to predict the variation in rain fades characteristics at C,Ku,Ka and ,V-bands in different parts of the country using The International Telecommunication Union Radio wave Propagation models (ITU-RP). Results show agreement with the model by Chieko and Yoshio .